2021
DOI: 10.3390/brainsci11060732
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Effects of the Amount of Training on Sensitivity of Distinct Actions to Reward Devaluation

Abstract: Shifting between goal-directed and habitual behaviors is essential for daily functioning. An inability to do so is associated with various clinical conditions, such as obsessive–compulsive disorder (OCD). Here we developed a new behavioral model in mice allowing us to produce and examine the development of different behaviors under goal-directed or habitual control. By using overtraining of instrumental associations between two levers and two rewards, and later devaluating one of the rewards, we differentiate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Using a novel learning paradigm, they were able to examine how different behaviors are affected by different behavioral control mechanisms, representing either goal-directed or goal-insensitive habitual control. The authors demonstrated that excessive practice of instrumental conditioning may form habitual patterns that cannot be amended, even when resulting in a noxious outcome, in contrast to consummatory or Pavlovian behaviors that maintain the ability to adapt [ 7 ].…”
mentioning
confidence: 99%
“…Using a novel learning paradigm, they were able to examine how different behaviors are affected by different behavioral control mechanisms, representing either goal-directed or goal-insensitive habitual control. The authors demonstrated that excessive practice of instrumental conditioning may form habitual patterns that cannot be amended, even when resulting in a noxious outcome, in contrast to consummatory or Pavlovian behaviors that maintain the ability to adapt [ 7 ].…”
mentioning
confidence: 99%